The Effect of Brand Awareness, Brand Image, and Product Quality on Consumer Satisfaction of Oppo Smartphone Users in Pekanbaru - Christian, Christian; Wijaya, Evelyn (Nexus Synergy: A Business Perspective, 2024)
The development of communication technology has undergone very significant changes ranging from simple to modern. One of the visible developments in communication technology is the Smartphone. This study aims to determine and analyze the effect of Brand Awareness, Brand Image, and Product Quality on OPPO Smartphone Users in Pekanbaru. The population of this study is consumers who have OPPO smartphones in Pekanbaru City. Sampling in this study used the Accidental Sampling method, so the sample in this study was 120 respondents. Methods of collecting data through questionnaires and interviews. The analysis technique in this research is the Structural Equation Model (SEM) with the help of Smart Partial Least Square (PLS) 3.0 software. Based on the results obtained in this study, the variables of Brand Awareness, Brand Image, and Product Quality have a positive and significant influence on consumer satisfaction.